The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1901/jeab.1992.58-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Delayed Reinforcement on Infant Vocalization Rate

Abstract: Three previous studies have failed to demonstrate conditioning in infants using a 3-s delay of reinforcement. The effects of a delayed reinforcement schedule on vocalization rates therefore were explored in a single-subject repeated-reversal experimental design for 3 4-to 6-month-old normally developing infants. Each infant received delayed social reinforcement from his or her parent for vocalizing. The comparison condition was a schedule of differential reinforcement of behavior other than vocalizations to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…In both experiments, delayed reinforcement resulted in a systematic increase in the vocalization rates of infants. These results are consistent with those of Reeve et al (1992), but not with some of the earlier literature on infants (Millar & Watson, 1979;Ramey & Ourth, 1971). As in the Reeve et al study, each infant in the current experiments was presented with each experimental condition over many daily 12-min sessions, and conditioning with delayed reinforcement was obtained for delays of 3 s and longer.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…In both experiments, delayed reinforcement resulted in a systematic increase in the vocalization rates of infants. These results are consistent with those of Reeve et al (1992), but not with some of the earlier literature on infants (Millar & Watson, 1979;Ramey & Ourth, 1971). As in the Reeve et al study, each infant in the current experiments was presented with each experimental condition over many daily 12-min sessions, and conditioning with delayed reinforcement was obtained for delays of 3 s and longer.…”
Section: Discussionsupporting
confidence: 84%
“…Dews (1960) demonstrated an increase in responding during delayed reinforcement, and Pierce et al (1972) showed no difference between DRO and delayed reinforcement. In studies with infants, DRO was used as a control condition by Reeve et al (1992), and conditioning was demonstrated with delayed reinforcement. Although a programmed DRO schedule should produce little adventitious reinforcement of the target response, analysis of reinforcement rates may nevertheless clarify the reason for the contradictory data of Pierce et al (1972) and other researchers using DRO schedules.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Delayed reinforcement can be arranged to establish and maintain responding in the absence of shaping or other training (e.g., Lattal & Williams, 1997). This phenomenon has been demonstrated across several species, including rats and pigeons (Lattal & Gleeson, 1990;Wilkenfield, Nickel, Blakely, & Poling, 1992), Siamese fighting fish (Lattal & Metzger, 1994), and human infants (Reeve, Reeve, Brown, Brown, & Poulson, 1992). The findings of such studies consistently demonstrate that unsignaled delayed reinforcement produces low but persistent rates of responding (Critchfield & Lattal, 1993;Lattal & Gleeson, 1990;Wilkenfield et al, 1992).…”
Section: Basic Research Related To Delayed Reinforcementmentioning
confidence: 79%